Applying Kruskal's Algorithm in Supply Chain Management for Cost-Effective Network Optimization - Pooja Pandya; Gunja Dave; Nirali (International Journal of Algorithms Design and Analysis Review, 2025)
Transportation route optimization and cost reduction are major difficulties in today's dynamic and complicated supply chain systems. To produce economical and effective network designs, this study investigates the use of Kruskal's algorithm for supply chain network optimization. The algorithm guarantees that all supply chain nodes, including delivery hubs, warehouses, and distribution centers, relate to the lowest possible total transportation cost by building the minimum spanning tree (MST). The study shows how Kruskal's algorithm systematically chooses the most economical routes, resulting in notable cost savings and improved operational effectiveness. This study demonstrates the algorithm’s ease of use, scalability, and adaptability through real-world examples and comparative analysis, making it a useful tool for supply chain management. The results highlight how crucial it is to gather precise data and consider other elements like delivery schedules and capacity limitations in order to guarantee thorough optimization. All things considered, this study highlights Kruskal's algorithm as a crucial tool for developing effective, economical supply chain networks.
Keywords: Kruskal's algorithm; Supply chain management; algorithmic optimization; cost-effective supply chain; graph theory in supply chain; minimum spanning tree (MST); supply chain network optimization; supply chain optimization; transportation cost reduction; transportation routes